2006
DOI: 10.1124/dmd.106.011056
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Human Cytochrome P450 Reductase as a Potential Biomarker for Mitomycin C-Induced Cytotoxicity

Abstract: ABSTRACT:The importance of genetic variation in clinical response to various drugs is now well recognized. Identification of genetic biomarkers that can predict efficacy and toxicity of chemotherapeutic drugs in cancer patients holds great promise in treatment improvement and cost reduction. Mitomycin C (MMC) is a common anticancer drug used for the treatment of numerous types of tumors. Metabolismmediated activation, by either one-electron or two-electron reduction, plays a critical role in the chemotherapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…WT ⌬66 exhibited a k cat /K m NADPH ϭ 220 min Ϫ1 M Ϫ1 , whereas WT holo was nearly three times more efficient with a k cat /K m NADPH ϭ 650 min Ϫ1 M Ϫ1 . Reaction rates were beneath the limit of detection when either ⌬66 or holo Y181D was assayed, in agreement with previously published findings using bacterially expressed, N-truncated proteins Huang et al, 2005;Wang et al, 2007). On the other hand, purified Y181D was shown by HPLC to retain a small proportion of bound FMN, which would hypothetically confer at least some small amount of NCR activity.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…WT ⌬66 exhibited a k cat /K m NADPH ϭ 220 min Ϫ1 M Ϫ1 , whereas WT holo was nearly three times more efficient with a k cat /K m NADPH ϭ 650 min Ϫ1 M Ϫ1 . Reaction rates were beneath the limit of detection when either ⌬66 or holo Y181D was assayed, in agreement with previously published findings using bacterially expressed, N-truncated proteins Huang et al, 2005;Wang et al, 2007). On the other hand, purified Y181D was shown by HPLC to retain a small proportion of bound FMN, which would hypothetically confer at least some small amount of NCR activity.…”
Section: Resultssupporting
confidence: 78%
“…A number of studies, including the original from Arlt et al (2004) detailing the discovery of the exon 5 POR 541T3 G mutation, have shown the catalytic incompetence of Y181D-substituted CYPOR using various assays and means of recombinant protein expression (Huang et al, 2005;Wang et al, 2007;Agrawal et al, 2008). Before the discovery of POR deficiency as a cause of human disease, Shen et al (1989) showed that the orthologous Y178D variant of rat CYPOR, recombinantly expressed and purified, was unable to catalyze NCR activity because of loss of FMN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ample evidence proves that bioreductive activation of the antitumor drugs: doxorubicin (15), tirapazamine (16), and indoloquinone (EO9) (17) by the cellular oxidoreductases P450R leads to significant increases in their covalent binding to DNA and cytotoxic activity against tumour cells (Bailey et al 2001;Bartoszek and Wolf 1992;Chinje et al 1999;Cowen et al 2003;Cullinane et al 1994;Kostrzewa-Nowak et al 2005;Patterson et al 1995Patterson et al , 1997Skladanowski and Konopa 1994). The bioreduction of mitomycin C(MMC) (18) by P450R leads to the formation of free radicals which cause lipid peroxidation, protein and DNA damage, and, ultimately cell death (Belcourt et al 1998;Joseph et al 1996;Kappus 1986;Wang et al 2007). Similarly, the toxicity of 5-fluorouracil (19) is enhanced by P450R through reactive oxygen species (ROS) production and NADPH depletion in P450R-overexpressing cells (Martinez et al 2008).…”
Section: One and Two Electron Reductions Of Quinonesmentioning
confidence: 98%
“…The variability in scarring is the main factor involved in cases of overcorrection, undercorrection, stromal opacity, and other possible complications of these surgeries. (5) Depending on the level of desired correction, corneal scarring and stimuli for the fibrotic response may be stronger after PRK. In fact, the main effect is the structural and functional defects of the base epithelial membrane occurring when there is great irregularity of the surface, after high corrections.…”
mentioning
confidence: 99%